Avaliação de polimorfismos nos genes FOXO3A, AMPK EPOMC e sua relação com a obesidade mórbida - Cinthia Vila Nova Santana (2013)
Morbid obesity (MO) is a metabolic disorder that affects people worldwide. Excessive fat accumulation in MO patients is frequently found to increase the risk for several co-morbidities, including cardiovascular disease and type 2 diabetes. Although environmental factors are well-known to play a role in MO risk, accumulate evidence has also highlighted that inherited factors may predispose subjects to MO. Because the genes FOXO3a (forkhead box O 3a transcription factor), AMPK (activated protein kinase) and POMC (proopiomelanocortin) encode regulatory proteins that act on both energy metabolism and feeding beha vior, here we have addressed whether polymorphisms in these genes are risk factors to MO. Therefore, the genetic frequencies of rs1536057, rs2802292, rs3813498, rs1935952 (FOXO3a), rs1442760, rs1036851, rs1348316, rs11584787 (AMPK ) and rs934778, rs6545975 (POMC) were evaluated in 242 morbidly obese patients (BMI 40 kg/m²) and 283 healthy subjects (BMI 24.99 kg/m²). DNA samples were isolated from blood and genotyping was performed by TaqMan-based assays. Our findings revealed that out of 10 polymorphisms analyzed, only allele and genotype frequencies of rs1536057 (FOXO3a), rs103685 (AMPK), rs934778 and rs6545975 (POMC) were heterogeneously distributed between morbid obesity and healthy subjects groups. Furthermore, epistasis analysis did not show any significant model of genetic interaction influencing the susceptibility to morbid obesity. Results of this study for the first time provide data on distribution of FOXO3a, AMPK and POMC polymorphisms in the Brazilian population and suggest that selected geneti c variants may confer risk of morbid obesity in humans.